2022
DOI: 10.1002/aenm.202202719
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Co‐Free Layered Oxide Cathode that Affords Fast‐Charging Lithium‐Ion Batteries for Electric Vehicles

Abstract: The development of Co‐free Li[NixMn1−x]O2 cathodes for lithium‐ion batteries (LIBs) that can supersede Co‐containing Li[NixCoyMn1−x−y]O2 and Li[NixCoyAl1−x−y]O2 cathodes is considered a priority as Co is associated with price volatility, environmental concerns, and human rights violations. However, the complete removal of Co from cathodes for LIBs is difficult because Co‐free cathodes suffer from structural instability and inferior capacity. In this study, a morphology‐engineering approach is used to develop a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…As detailed earlier, the 75%MO had the greatest hardness among the 3 AAM electrode compositions. It was speculated that the greater hardness may have mitigated particle cracking or detachment processes, which would result in formation of new interphase (and consequently additional SEI) 64 relative to the 0%MO and 100%MO.…”
Section: Cycle Stability Characterizationmentioning
confidence: 99%
“…As detailed earlier, the 75%MO had the greatest hardness among the 3 AAM electrode compositions. It was speculated that the greater hardness may have mitigated particle cracking or detachment processes, which would result in formation of new interphase (and consequently additional SEI) 64 relative to the 0%MO and 100%MO.…”
Section: Cycle Stability Characterizationmentioning
confidence: 99%
“…The positive correlation of Ni and Zr will endow particles with structural stability, by decreasing the probability of intergranular cracks. 50 Besides, the stable structure avoids the exposure of the internal surface and the aggravation of side reactions. Besides, the XPS results (Figure S16 ), 51 O 1s (M−O, ROLi, C�O, C−O, Li x PF y O 2 ), 52 F 1s (LiF, Li x PF y O 2 / Li x PF y ), 53 and P 2p (Li x PF y O 2 , Li x PF y ).…”
Section: Mechanismmentioning
confidence: 99%
“…[21,22] In addition to chemical doping, the phase-specific particle morphology in this system can be influenced via a structural engineering approach exploiting synthesis conditions. [8,13,23] For example, we recently demonstrated that it is possible to achieve a core-shell morphology in Li 1.1 Ni 0.35 Mn 0.55 O 2 with the Ni-rich R-phase preferentially segregated to particle surfaces by combining spray-pyrolysis with a post-deposition calcination at 900 °C. [24] This microstructure correlated to an enhanced electrode performance, with the optimal synthesis parameters delivering 160 and 100 mAhg −1 at C/3 and 1C, respectively, with 80% capacity retention after 150 cycles.…”
Section: Introductionmentioning
confidence: 99%